2014
DOI: 10.4236/ojmm.2014.42012
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Agents Responsible for Diarrheal Infections in Flood Victims: A Study from Karachi, Pakistan

Abstract: The present study was aimed to determine the frequency of water borne diarrheal infections and gastroenteritis in two of the flood affected camps of Karachi and nearby areas. Each year approximately, 579,732 people are adversely affected by this phenomenon, putting Pakistan 9th in terms of flood-affected countries worldwide. Patients and Methods: All patients suffering from diarrhea (more than 3 stools per day for the last 2 days), abdominal pain, vomiting or fever who were residing in the camps were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Poor water and sewage systems are considered to be the main reasons for Hepatitis A and E infection endemic in Pakistan [20]. The results of the current study are in line with previous reports indicating high pervasiveness of diarrheal viruses in the developing countries of Asia, such as Pakistan, Bangladesh, India, Nepal, Vietnam, and even in China [21]. Poor distribution of water and the open drainage system in Peshawar; especially during the raining season when an overflow of drainage water can contaminate not only the drinking water pipeline, but also viruses accumulate on the ground water resources [22] and are cause for great alarm.…”
Section: Discussionsupporting
confidence: 91%
“…Poor water and sewage systems are considered to be the main reasons for Hepatitis A and E infection endemic in Pakistan [20]. The results of the current study are in line with previous reports indicating high pervasiveness of diarrheal viruses in the developing countries of Asia, such as Pakistan, Bangladesh, India, Nepal, Vietnam, and even in China [21]. Poor distribution of water and the open drainage system in Peshawar; especially during the raining season when an overflow of drainage water can contaminate not only the drinking water pipeline, but also viruses accumulate on the ground water resources [22] and are cause for great alarm.…”
Section: Discussionsupporting
confidence: 91%
“…Analysis data showed that in presented study alkalinity ranged from 120-513 mg/L. Literature showed that elevated concentration of chloride may create problems in throat and digestive system along with imparting saline taste and corrosion problems [25]. Presented data showed that Cl ranged from 23-8575 mg/l and overall 49% water samples have high concentration of Cl than GVs.…”
Section: Physico-chemical Parametersmentioning
confidence: 67%
“…Similarly, higher contents of Cl in drinking water may create problems in throat and digestive system along with imparting saline taste and corrosion [23]. Alkalinity is also an important parameter of water quality but its concentration beyond certain limit causes many problems like hardness, kidney stone, gas trouble, damage of metallic pipes and severe irritation of skin, eyes and mucous membrane [24].…”
Section: Minerals Assessmentmentioning
confidence: 99%